Developing Speaking Skills in Lower-secondary Students: Focus on interaction - Vosáhlová, Simona (Univerzita Pardubice, 2020)
This bachelor paper deals with the topic of developing speaking skills in lower-secondary students with a focus on interaction. The theoretical part explains and defines English language teaching in a context of foreign language teaching, communicative competence, speaking skills, interaction, and the role of tasks and textbooks in ELT. It also discussed interaction patterns, activity types and functionalities, the theory of task implementation, and aims. These four categories are the basis of the analysis realized in the practical part of this paper. List of selected tasks from a textbook Project 2 is analyzed and the data gained are evaluated and diagnosed. The final outcome of the paper is the textbook evaluation in the context of the paper's thesis.
Rozvoj komunikačních dovedností u žáků 2. stupně základní školy: Zaměření na interakci
Keywords: řečové dovednosti; angličtina jako druhý jazyk; hodnocení učebnic; interakce; speaking skills; English as a foreign language; textbook evaluation; interaction